(untitled) (Hekima Review, 1994)
This essay aims at exploring the controversial issue of the "Permanence of Orders". On one side, we have those who affirm the permanence not so much in an ontological change but God's permanent commitment to us arid our commitment to God as a response, others particularly liberation theologians deny. the permanence on the basis of the historical development of the understanding of the orders and the theology of charisma addressed to a need. Doctrinally, the documents of the Church affirm the "indelible character'' of the orders but without giving any definition of the nature of this character.